Home environmental and lifestyle factors associated with asthma, rhinitis and wheeze in children in Beijing, China. (January 2020) - Huang, Shaodan; Garshick, Eric; Weschler, Louise B.; Hong, Chuan; Li, Jing; Li, Linyan; Qu, Fang; Gao, Dewen; Zhou, Yanmin; Sundell, Jan; Zhang, Yinping; Koutrakis, Petros
Abstract: Background: The prevalence of asthma and allergic diseases has increased rapidly in urban China since 2000. There has been limited study of associations between home environmental and lifestyle factors with asthma and symptoms of allergic disease in China. Methods: In a cross-sectional analysis of 2214 children in Beijing, we applied a two-step hybrid Least Absolute Shrinkage and Selection Operator (LASSO) algorithm to identify environmental and lifestyle-related factors associated with asthma, rhinitis and wheeze from a wide range of candidates. We used group LASSO to select variables, using cross-validation as the criterion. Effect estimates were then calculated using adaptive LASSO. Model performance was assessed using Area Under the Curve (AUC) values. Results: We found a number of environmental and lifestyle-related factors significantly associated with asthma, rhinitis or wheeze, which changed the probability of asthma, rhinitis or wheeze from −5.76% (95%CI: −7.74%, −3.79%) to 27.4% (95%CI: 16.6%, 38.3%). The three factors associated with the largest change in probability of asthma were short birth length, carpeted floor and paternal allergy; for rhinitis they were maternal smoking during pregnancy, paternal allergy and living close to industrial area; and for wheeze they were carpeted floor, short birth length and maternal allergy. Other home environmental risk factors identified were living close to a highway, industrial area or river, sharing bedroom, cooking with gas, furry pets, cockroaches, incense, printer/photocopier, TV, damp, and window condensation in winter. Lifestyle-related risk factors were child caretakers other than parents, and age<3 for the day-care. Other risk factors included use of antibiotics, and mother's occupation. Major protective factors for wheeze were living in a rural/suburban region, air conditioner use, and mother's occupation in healthcare. Conclusions: Our findings suggest that changes in lifestyle and indoor environments associated with the urbanization and industrialization of China are associated with asthma, rhinitis, and wheeze in children. Graphical abstract: Image 1 Highlights: We investigated home environmental and lifestyle factors associated with children's allergy. We used a global variable procedure (LASSO) to select potential influencing factors. We assessed associated factors in common for asthma, wheeze and rhinitis. We calculated the probability change due to each risk factor. Our model has sufficient statistic power and strong predicting performance.